Violation of lockdown norms and peaks in daily number of positive cases to COVID-19 in Italy [version 1; peer review: 2 approved] - Gabriele Ruiu; Maria Laura Ruiu (Emerald Open Research, 2020)
Italy has been the first Western Country to suffer a massive outbreak of COVID-19. Starting from the 11st of March 2020, the Italian Government approved a series of emergency restrictive measures to limit people’s movement and social contacts. The aim of this short paper is to test if the number of norm-violations (related to people’s movement) might contribute to the peaks of new COVID-19 positives after few days. We show that peaks in the violations of the lockdown norms correspond to peaks in new positive cases about 6 days later.